In Vitro Proof of Concept Evaluation of the Radial Force Generated by a Novel Mechanical Thrombectomy Device that Incorporates Controlled, Expandable Wire Spheres - Horowitz, Michael Bruce; Sattell, Jack B.; Repko, Brandon; Le, Hieu; Bobo, Benjamin (Cardiology and Cardiovascular Medicine, 2024)
Background: This study measured the radial force (RF) imparted upon a vessel wall when a manually controlled, expandable wire sphere that was incorporated into a mechanical thrombectomy device was expanded to oppose the vessel wall. Results would help determine the device’s safety profile with regards to risk of vessel rupture during device deployment. Methods: A novel proprietary manually controlled, expandable, wire sphere (Retriever Medical, Las Vegas, NV, USA) was advanced in its collapsed form into an MSI RX 650 RF Tester (Machine Solutions Inc., Flagstaff, AZ, USA). The device cylinder iris was adjusted to provide cylinder test diameters of 5 mm, 7.5 mm and 10 mm. RF exerted by the expandable sphere was measured at each of the above diameters. The testing was performed with the thrombectomy device delivered along both a straight and tortuous course to determine whether or not pathway complexity influenced the terminal RF generated. Results: Maximum RF generated by the wire sphere was 22 Newtons (N). RF increased as cylinder and wire sphere diameter increased from 5 – 10 mm. No significant differences in generated RF were detected when the straight and tortuous device delivery pathway were compared. Conclusion: The RF generated by the novel, proprietary, manually controlled, expandable wire sphere designed to perform mechanical thrombectomy fell far below the established N required to cause rupture of the saphenous vein and pulmonary artery. This information, combined with our prior published work showing no venous endothelial damage following porcine In Vivo sphere manipulation, provides additional evidence supporting the device’s favorable safety profile. Trial Registration: This article does not report the results of a health care intervention on human subjects.